Perancangan Program Administrasi Rawat Jalan Pada Rumah Sakit Ibu Dan Anak Ibnu Sina - Norma Yunita; Muhamad Angga Maulana; Daning Nur Sulistyowati; Maruloh Maruloh (JURNAL TEKNIK KOMPUTER, 2021)
It is undeniable that technology is developing very fast. All the activities in the company or agency have shifted to computerization. The hospital is no exception. In providing health services to patients, hospitals are required to be able to do it quickly, precisely, and efficiently by not reducing the quality standard of service. The use of conventional systems makes hospitals hampered in the implementation of service activities. Whereas hospitals have an obligation to create, implement and maintain quality standards of health services in hospitals as a reference in serving patients. At the Ibnu Sina Mother and Child Hospital, in the service of patients for outpatient registration they still use the conventional system so that it is necessary to transition the system from conventional to computerized in order to maintain the quality of service. The system needed, namely registration and management of outpatient data. The system is prepared using the waterfall method as a method of software development and implementing the system in the form of a desktop application using the programming language Codeigniter 3, PHP 7, and Bootstrap 4. It is expected that with this system, hospitals can run better and can improve hospital quality in services so that patients feel satisfied with the services provided by the hospital.